Public Utility Reform : What Lessons Can We Learn from IEG Evaluations in the Energy and Water Sectors? - World Bank (World Bank, Washington, DC, 2021)
This synthesis provides a review of operationally relevant findings and lessons from World Bank-supported utility reforms in the energy and water sectors, as identified in IEG evaluation products. The report summarizes the IEG evidence of what worked and what did not work, and why, in WB support of public utility reforms in its client countries. It identifies two fundamental areas of utility reform – improving institutional accountability and strengthening financial viability. The first involves measures to reform institutional arrangements, policies, and regulations; sector planning, utility management, capacity, and skills; and creating the framework for private investment. The second requires strengthening cost recovery, commercial viability, and operational efficiency. The report compares the effectiveness of Bank instruments (DPOs and IPFs) across selected financial viability targets. It identifies lessons for each sector and cross-cutting lessons for both energy and water operations centered on promoting financial and operational discipline (regardless of private or public ownership), and institutional governance and accountability.